Parametric Optimization and Experimental Validation for Nonlinear Characteristics of Passenger Car Suspension System - Mohd, Avesh; Srivastava, Rajeev (Periodica Polytechnica Transportation Engineering, 2021)
The study deals with the design of the automotive suspension system to better dynamic characteristics in an uncertain operating atmosphere. Vehicle design parameters are to be optimized to achieve better passengers comfort, vehicle body stability, and road holding as the measure of suspension system performance improvement. The design of experiments gives the optimum parametric combination in the domain on the basis of vertical body acceleration data obtained by simulation of a 2-DOF nonlinear quarter car model. Moreover, the nonlinear hysteric behavior foremost design parameters have been characterized through the theoretical and experimental analysis in order to validate the design and to check the analogical viability of the derived model. Finally, the proposed methodology ascertains the optimum design of the suspension system in the time and cost-effective manner. The developed passive design of car suspension system exhibits excellent vibrational characteristics and convinces the acceptable range of vehicle vibration as suggested by ISO-2631-1997.